2015
DOI: 10.3126/ijasbt.v3i3.13123
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Divergence of Snow Trout (Schizothorax Richardsonii, Gray 1932) from Rivers of Nepal with Insights from a Morphometric Analysis

Abstract: Asala or snow trout (Schizothorax richardsonii, Cyprinidae), one of highly valued freshwater fish of Transhimalayan regions, is distributed in upper reaches of all major river systems of Nepal. Morphometric diversification between six river populations of S. richardsonii was examined to identify intraspecific unit for enabling better management of the resources. Significant differences were observed in 17 measured morphometric characters of 207 specimens among the six river populations. Multivariate analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Only slight differences in the shape and size of the ceratohyal and epihyal were noted, with the epihyal of S. richardsonii being smaller than S. plagiostomus. Other similar observations regarding the morphological variations were noted by Wagle et al (2015) , who reported that for S. richardsonii , all the parameters were undoubtedly interrelated with total length and head length; the current study also obtained similar results ( Figures 5A,B ). Thus, it is concluded that the anal fin length and lips resolve the phenotypic problem of differentiating between these two species.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Only slight differences in the shape and size of the ceratohyal and epihyal were noted, with the epihyal of S. richardsonii being smaller than S. plagiostomus. Other similar observations regarding the morphological variations were noted by Wagle et al (2015) , who reported that for S. richardsonii , all the parameters were undoubtedly interrelated with total length and head length; the current study also obtained similar results ( Figures 5A,B ). Thus, it is concluded that the anal fin length and lips resolve the phenotypic problem of differentiating between these two species.…”
Section: Discussionsupporting
confidence: 91%
“…The number of inferior pharyngeal teeth in both species was the same (4, 3, 2/2, 3, 4). A lot of work has been reported favoring the current results (Misra et al, 1980;Negi and Negi, 2010;Mir et al, 2013a;Wagle et al, 2015;Wani et al, 2018;Kamboj and Kamboj, 2019). Misra et al (1980) revealed that both S. richardsonii and S. plagiostomus had the same number of teeth.…”
Section: Frontiers In Geneticsmentioning
confidence: 53%
“…also reported significant differences (p<0.05 or <0.001) in four (Maximum Body Height, Pre-orbital Length, Peduncle Length and Maxillary Barbel Length) of 9 morphometric variations in Labeo calbasu populations collected from the Jamuna, the Halda and a hatchery in Bangladesh. Many other authors have also reported similar results like Parvej et al (2014) in Eutropiichthys vacha; Siddik et al (2016) in Sillaginopsis panijus; Wagle et al (2015) in Schizothorax richarsonii and Esmaeili et al (2011) in Alburnoides qanati. Fagbuaro et al (2015) reported significant differences in Clarius gariepinus from Nigeria; differences were attributed to food, environmental conditions and type of habitat.…”
Section: Resultssupporting
confidence: 62%
“…Morphological adaptation of stream fish is mostly on the locomotion part, consisting of a variation on the abdominal shape, caudal regions, and fins (Shuai et al, 2018;Hanif et al, 2019). The slender body of stream fish is crucial to enhance the ability to swim against the stream (Mu et al, 2019;Wagle et al, 2015). Dunn et al (2020) reported population morphological variations of Galaxias brevipinnis, Galaxias gollumoides, and Galaxias Vulgaris in lotic habitats have a slender body to their lentic-habitats counterparts.…”
Section: Discussionmentioning
confidence: 99%